The Effectiveness of Preparing Local Government Implementation Reports (LPPD) in Improving the Accountability of Local Government Implementation in Pesawaran Regency, Lampung Province - Rahman, Rifky Arief (SAINTIS Publishing, 2025)
This study aims to analyse the effectiveness of the preparation of the Local Government Implementation Report (LPPD) in improving the accountability of local government administration in Pesawaran Regency, Lampung Province. This research uses Duncan's (1973) theory of effectiveness which includes three main dimensions, namely goal achievement, integration, and adaptation. The research method used is descriptive qualitative with data collection techniques through interviews, documentation studies, and direct observation. The results showed that the effectiveness of LPPD preparation in Pesawaran Regency still faced several obstacles. In the aspect of achieving goals, the inconsistency of the achievement of performance indicators causes the report not to be filled optimally. In the aspect of integration, the lack of communication intensity of regional apparatus hinders the completeness and accuracy of the data collected. Meanwhile, in the aspect of adaptation, local governments have not been optimal in adjusting to the regulations and reporting schedules set by the central government. To overcome these obstacles, a number of strategies are needed, such as increasing the competence of human resources through technical training, strengthening inter-OPD coordination, and instilling the commitment of OPD leaders to the preparation of LPPD. Through these efforts, it is expected that the effectiveness of LPPD preparation can be improved, so that the accountability of local government administration in Pesawaran Regency can be achieved optimally.